Introduction to recreation services for people with disabilities a person-centered approach - Bullock, Charles C; Mahon, Michael J. (Sagamore Publishing, 2016)
Introduction to recreation services for people with disabilities continues to reflect a broad-based explanation of the role of practitioners in the interrelated fields of therapeutic recreation, inclusive recreation, and special recreation. This fourth edition represents a major revision, including the most current research and thinking about the interdisciplinary fields of recreation and disability studies. This book is intended to be an introductory text for all students in parks and recreation/leisure studies departments. Every student, whether she or he intends to work in a provincial park or a state hospital, a community recreation center or a community mental health center, a public school or a cruise ship, needs a basic level of knowledge about people with disabilities. The central theme of this book is that people with disabilities are people who have the same needs and wants as anyone else and deserve the right to be at the center of their services. Each person with a disability is a person first, not a disability. Recreation services must be centered around the person who is being served. That is, whether treatment-oriented recreation therapy, goal-oriented special recreation, or activity-oriented inclusive recreation, it is the person and not the professional or even the activity that must be at the center of service delivery